2018
DOI: 10.1021/acsami.8b11201
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic SiC/CNTs Coatings with Photothermal Deicing and Passive Anti-Icing Properties

Abstract: For faster and greener anti-icing/deicing, a new generation of anti-icing materials are expected to possess both passive anti-icing properties and active deicing properties. The photothermal effect of carbon nanotubes (CNTs) is used in the field of photothermal cancer therapy, while the application in anti-icing/deicing is seldom investigated. Superhydrophobic SiC/CNTs coatings with photothermal deicing and passive anti-icing properties were first prepared by a simple spray-coating method. The results of 3D pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(133 citation statements)
references
References 34 publications
0
133
0
Order By: Relevance
“…by utilizing ample environmental light and environmental friendliness without harmful chemicals (19)(20)(21)(22)(23). Recently, it has been shown that plasmonic (21,24,25), magnetic particles (20,26), and carbon nanomaterials (26,27) can be utilized in photothermal surfaces to generate heat from photo/solar energy and melt accumulated ice. However, there are limitations and remaining challenges.…”
Section: Significancementioning
confidence: 99%
“…by utilizing ample environmental light and environmental friendliness without harmful chemicals (19)(20)(21)(22)(23). Recently, it has been shown that plasmonic (21,24,25), magnetic particles (20,26), and carbon nanomaterials (26,27) can be utilized in photothermal surfaces to generate heat from photo/solar energy and melt accumulated ice. However, there are limitations and remaining challenges.…”
Section: Significancementioning
confidence: 99%
“…Nevertheless, the adhesion force between the frozen water droplet and modified silicone rubber surface in the parallel and vertical directions is reduced to 1.1 and 2.3 N, respectively. The frozen droplet has a smaller liquid–solid area on the hierarchical nanostructured surface, thereby reducing the ice adhesion force 29 . The above self‐cleaning and anti‐icing properties make the modified surface can effectively reduce the damage caused by surface pollution, ice formation, and other natural factors when applied to power lines, sealing elements, automotive, and aviation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 139 ] Jiang et al fabricated a superhydrophobic SiC/CNT coating by spray coating, in which CNTs provided both a superhydrophobic structure and photothermal layer. [ 140 ] The surface temperature could increase rapidly under near infrared irradiation, and the generated heat was transferred fast to the surroundings due to the good thermal conductivity of CNTs. The deicing performance could be further enhanced by combining the photothermal with electrothermal effects using a conductive CNT‐based coating.…”
Section: Sustainable Applications Of Photothermal Materialsmentioning
confidence: 99%